2012
DOI: 10.17221/6311-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

The spinal nerves forming the brachial plexus in mole-rats (Spalax leucodon)

Abstract: ABSTRACT:In this study, the brachial plexus in the mole-rat was investigated. Six adult mole-rats were used and the brachial plexus of each was dissected. It was found that the brachial plexus in the mole-rat was formed by the rami ventralis of C5. A single root was formed from a major part of the ramus ventralis of C5 and through the joining of the whole of the ramus ventralis of C6, C7, C8 and T1. Thus, in mole-rats, the spinal nerves forming the brachial plexus and the joining of these spinal nerves to each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
(22 reference statements)
2
6
0
Order By: Relevance
“…While Angelica-Almeida et al (2013) reported that the plexus originates between C4 and T1 in rats, Ozbag et al (2009) suggested that it is between C5 and T1 in the same animals. On the other hand, a mole-rat (Aydin and Karan, 2012) plexus brachialis study showed similar results to those of Ozbag et al (2009). In the present study on the red fox, we showed that the plexus brachialis originated from C5, C6, C7, C8, T1 and T2, similar to that seen in cats (Mencalha et al, 2014) and the chinchilla (Cevik-Demirkan et al, 2007).…”
Section: Discussionsupporting
confidence: 86%
“…While Angelica-Almeida et al (2013) reported that the plexus originates between C4 and T1 in rats, Ozbag et al (2009) suggested that it is between C5 and T1 in the same animals. On the other hand, a mole-rat (Aydin and Karan, 2012) plexus brachialis study showed similar results to those of Ozbag et al (2009). In the present study on the red fox, we showed that the plexus brachialis originated from C5, C6, C7, C8, T1 and T2, similar to that seen in cats (Mencalha et al, 2014) and the chinchilla (Cevik-Demirkan et al, 2007).…”
Section: Discussionsupporting
confidence: 86%
“…The brachial plexus of the AGR was formed mainly by the ventral rami of C5, C6, C7, C8 and T1. This result is similar to what was observed in some rodents such as wistar rats [ (Ozbag et al, 2009;Uzun et al, 2001), chinchilla (Chinchilla lanigera) (Cevik -Demirka n et al, 2007), mole-rat (Spalax leucodon) (Ayidin & Karan, 2012) and primates such as Owl monkey (Aotes trivirgatus) (Mizuno, 1966), Capuchin monkey (Cebus capucinus) (Mizuno, 1969), the rhesus monkey (Macaca mulatta) (Lu et al, 2013;Santo -Souza et al, 2016), common marmoset (Emura et al, 2017), humans (Guday et al, 2016) and the giant anteater (Myrmecophaga tridactyla) (Souza et al, 2013). The brachial plexus of some rodents like the red squirrel (Sciurus vulgaris) was noted to be formed by ventral branches of C5, C6, C7 and C8 without any contribution from the ventral branch of T1 (Ayidin, 2011).…”
Section: Discussionsupporting
confidence: 88%
“…It branches towards the biceps brachii, brachialis and coracobrachialis musculus, similar to the paca (Scavone et al 2008), and capybara (Fioretto et al 2003). Aydin and Karan (2012) described that the musculocutaneous nerve in the mole-rat branches towards the cutaneus antebrachi muscle, which was not found in the Spix's yellow-toothed cavy.…”
Section: Mazama Gouazoubiramentioning
confidence: 82%